Raman 18O-labeling of bacteria in visible and deep UV-ranges - Matanfack, Georgette Azemtsop; Pistiki, Aikaterini; Roesch, Petra; Popp, Jürgen (Journal of Biophotonics, 2021)
Raman stable isotope labeling with 2H, 13C or 15N has been reported as an elegant approach to investigate cellular metabolic activity, which is of great importance to reveal the functions of microorganisms in native environments. A new strategy termed Raman 18O-labeling was developed to probe the metabolic activity of bacteria. Raman 18O-labeling refers to the combination of Raman microspectroscopy with 18O-labeling using H218O. At an excitation wavelength of 532 nm, the incorporation of 18O into the amide I group of proteins and DNA/RNA bases was observed in Escherichia coli cells, while for an excitation wavelength electronically resonant with DNA or aromatic amino acid absorption at 244 nm 18O assimilation was detected using chemometric tools rather than visual inspection. Raman 18O-labeling at 532 nm combined with 2D correlation analysis confirmed the assimilation of 18O in proteins and nucleic acids and revealed the growth strategy of E. coli cells; they underwent protein synthesis followed by nucleic acid synthesis. Independent cultural replicates at different incubation times corroborated the reproducibility of these results. The variations in spectral features of 18O-labeled cells revealed changes in physiological information of cells. Hence, Raman 18O-labeling could provide a powerful tool to identify metabolically active bacterial cells.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 2D-correlation spectroscopy; bacterial cells; Raman microspectroscopy; stable isotope labeling